Mechanisms for the reduction of caffeine consumption: What, how and why. (1st July 2020) - Rodda, Simone; Booth, Natalia; McKean, Jessica; Chung, Anita; Park, Jennifer Jiyun; Ware, Paul
Highlights: Consumer initiated caffeine reduction techniques involve more than just fading. Behaviour change techniques are most frequently substitution and avoidance. Problem recognition involves seeking information and identification of harm. Harm is frequently reported as undermining health (e.g., poor sleep). Even though caffeine is a functional drug there are concerns about dependence. Abstract: Background: Anecdotal evidence suggests consumers of caffeine self-administer strategies to reduce consumption, but little is known of what these strategies are or how they are implemented. This study aimed to understand the lived experience of reducing caffeine consumption including specific techniques (what) and implementation strategies (how), harm and withdrawal symptoms (why). Methods: We developed a classification system through an inductive and deductive approach and applied it to a large dataset derived from online sources. Results: A total of 112 internet sources were identified, containing 2, 682 different strategies. The classification system identified 22 categories of Behaviour Change Techniques (BCT): 10 categories were directly aligned with a BCT, one was split into two categories (substance and behavioural substitution), six represented a cluster of BCT's (e.g., withdrawal management and maintaining momentum) and four appeared to uniquely represent a consumer perspective (e.g., realisation of a problem). The most common techniques were substance substitution, seek knowledge and information, avoidance of caffeine and identify prompts for change . The most frequently perceived benefit was the stimulating effects of caffeine and a feeling of mental alertness. The most frequently cited harms were sleep problems including insomnia and concerns about dependence (or addiction) to caffeine. We found 16 categories of withdrawal symptoms. The most frequently endorsed symptom was headaches, followed by fatigue, exhaustion and low energy. Conclusions: Consumers use a wide range of techniques when attempting to reduce caffeine consumption. Treatment approaches are focused on fading, but the current study found consumers most frequently focus on substance and behavioural substitution.